2017
DOI: 10.3390/ijms18030521
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab Is Equally Effective in Persistent Allergic Oral Corticosteroid-Dependent Asthma Caused by Either Seasonal or Perennial Allergens: A Pilot Study

Abstract: Omalizumab is marketed for chronic severe asthma patients who are allergic to perennial allergens. Our purpose was to investigate whether omalizumab is also effective in persistent severe asthma due to seasonal allergens. Thirty patients with oral corticosteroid-dependent asthma were treated with Omalizumab according to the dosing table. For each patient with asthma due to seasonal allergens, we recruited the next two consecutive patients with asthma due to perennial allergens. The dose of oral methyl predniso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…Benefits of omalizumab may extend up to 2–4 years, and the majority of omalizumab-treated patients may benefit for many years in terms of clinical, quality of life and health resource utilization outcomes [41]. Interestingly, a recent study showed that omalizumab offers the same clinical benefit in patients with persistent allergic asthma regardless of whether the asthma was caused by seasonal or perennial allergens [42].…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of omalizumab may extend up to 2–4 years, and the majority of omalizumab-treated patients may benefit for many years in terms of clinical, quality of life and health resource utilization outcomes [41]. Interestingly, a recent study showed that omalizumab offers the same clinical benefit in patients with persistent allergic asthma regardless of whether the asthma was caused by seasonal or perennial allergens [42].…”
Section: Discussionmentioning
confidence: 99%
“…to having a count of <150 cells/ µL ( Figure 1B). to either pollens or perennial allergens (23) . Omalizumab efficacy in non-allergic asthma, urticaria and eosinophilic oesophagitis further emphasises its ability to modulate complex immune cascades in so called 'non-allergic states' (24)(25)(26)(27) .…”
Section: Resultsmentioning
confidence: 99%
“…Omalizumab (OMA) (Xolair Novartis ® ), a murine immunoglobulin E (IgE) monoclonal antibody (mAb) blocking agent marketed since late 2006 , is currently recommended for unstable allergic GINA step IV and GINA step V asthma patients, before the administration of oral corticosteroids (OC) . Encouraging results with off‐label prescriptions of OMA have also been reported. OMA initially showed a sparing effect of inhaled corticoids , and two recent studies have also shown its oral corticosteroid‐sparing effect in severe allergic asthma patients .…”
Section: Introductionmentioning
confidence: 88%